Flavonoids as noncompetitive inhibitors of Dengue virus NS2B-NS3 protease: Inhibition kinetics and docking studies. Issue 3 (1st February 2015) - de Sousa, Lorena Ramos Freitas; Wu, Hongmei; Nebo, Liliane; Fernandes, João Batista; da Silva, Maria Fátima das Graças Fernandes; Kiefer, Werner; Kanitz, Manuel; Bodem, Jochen; Diederich, Wibke E.; Schirmeister, Tanja; Vieira, Paulo Cezar
Graphical abstract: Abstract: NS2B-NS3 is a serine protease of the Dengue virus considered a key target in the search for new antiviral drugs. In this study flavonoids were found to be inhibitors of NS2B-NS3 proteases of the Dengue virus serotypes 2 and 3 with IC50 values ranging from 15 to 44 μM. Agathisflavone (1 ) and myricetin (4 ) turned out to be noncompetitive inhibitors of dengue virus serotype 2 NS2B-NS3 protease with K i values of 11 and 4.7 μM, respectively. Docking studies propose a binding mode of the flavonoids in a specific allosteric binding site of the enzyme. Analysis of biomolecular interactions of quercetin (5 ) with NT647-NHS-labeled Dengue virus serotype 3 NS2B-NS3 protease by microscale thermophoresis experiments, yielded a dissociation constant K D of 20 μM. Our results help to understand the mechanism of inhibition of the Dengue virus serine protease by flavonoids, which is essential for the development of improved inhibitors.